(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Aim of the Study find out the assess effect of skill and plyometric training on Vo2 Max and attack hit among school volleyball players. The study was formulated as a true random group design, consisting of a pre test and post test. The subjects (n=60) were randomly assigned to three equal groups of fifteen The selected subjects were divided into three equal groups and each group consisted of twenty subjects. group-I skill training group experimental group-II – plyometric training group and control group respectively not participate in any special training apart from their regular physical education programme in the curriculum. Experimental period and after the experimental period of twelve weeks to determine the training effects. The subjects were re-tested after three weeks of cessation of training to found the detraining effects. To identify the significant difference among the groups due to training and detraining mean gain method was followed.